(3cJGH aj GdCOH hGdfhGOQs
(3ChdgG (B:s
(3eHJhQ GdChd , hChd eG ajg bhdg (B: (3bjd cGf PG Gdfhf GdeUQi ai UHGg TGWQkG , aHjfG gh jeTi Ydi TGWF fjd eUQ QCi QLdkG fGFekG hghScQGf s
(3BNQgG (B:s
(3hBNQg ef CHjGJ KdGKI bhdg (B: (3hdG CLYd GdMQeGf PfHkG BJjg Edi hEf YGbJ jOGc GdYhGFb Je GdcJGH HMeO Gddg hdWag s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfhGfGJ HNW fajS eLhOs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs